ANALISIS PELUANG BISNIS PADA INOVASI PRODUK EDUKASI FLASHCARD HUKUM BACAAN TAJWID - Kistanti; Ahmad Makhasin Ma’arif; Lathifatus Sa Diyyah; Rosalina; Ferida Rahmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Textbook-based Tajweed learning often leaves students bored and struggling to understand the material. This study aims to examine the effectiveness of flashcards in improving students' understanding of Tajweed reading rules at TPQ An-Nur Perum GPI Tanjungsari Kajen, as well as to explore business opportunities from this educational product innovation. The method used is a qualitative description involving 10 students as research subjects. Data collection was carried out through participatory observation, field notes, and documentation, then analyzed using the Miles and Huberman model. The research findings indicate that Tajweed flashcards can accelerate the memorization process, support independent learning, and increase student confidence through visual elements such as color and symbols. From a business perspective, this product shows good market potential among Islamic educational institutions and parents due to its practical, attractive design and strong physical durability. Thus, the innovation of Tajweed flashcards has proven effective as an interactive learning medium and offers attractive business opportunities in the Islamic education sector.